2006
DOI: 10.1021/la053030u
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Model for Adsorption of Polyatomics

Abstract: Multisite-occupancy adsorption is described by using a new formalism based on the occupation balance approximation (Roma, F.; Ramirez-Pastor, A. J.; Riccardo, J. L. J. Chem. Phys. 2001, 114, 10932). In this framework, the adsorption isotherm is characterized by a correction function C, which relates to the conditional probability of finding the ith empty site to a lattice with i - 1 already vacant sites. A simple semiempirical adsorption isotherm is proposed by approximating C as a combination of the correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Detailed comparisons between theoretical and simulation results of adsorption [9] showed that the GD approach fits the numerical data very well at low coverage, while the EA model behaves excellently at high coverage. Based on these findings, the semiempirical model for adsorption of polyatomics (SE) was developed [8,9]. The SE model is a combination of exact calculations in one dimension, its generalization to higher dimensions and the GD approximation with adequate weights.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Detailed comparisons between theoretical and simulation results of adsorption [9] showed that the GD approach fits the numerical data very well at low coverage, while the EA model behaves excellently at high coverage. Based on these findings, the semiempirical model for adsorption of polyatomics (SE) was developed [8,9]. The SE model is a combination of exact calculations in one dimension, its generalization to higher dimensions and the GD approximation with adequate weights.…”
Section: Introductionmentioning
confidence: 92%
“…The model, hereafter denoted EA, is based on exact forms of the thermodynamic functions of linear adsorbates in one dimension and its generalization to higher dimensions [7,8]. Detailed comparisons between theoretical and simulation results of adsorption [9] showed that the GD approach fits the numerical data very well at low coverage, while the EA model behaves excellently at high coverage. Based on these findings, the semiempirical model for adsorption of polyatomics (SE) was developed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The most well-known analytical approximation is: 1) the theory of Flory-Huggins [48,[55][56][57][58], which is a generalization of the theory of binary solutions of polymer molecules in a monomolecular solvent for the twodimensional case. The fact that in the framework of lattice gas model the problem of k-mer adsorption on homogeneous surfaces is isomorphic to the problem of binary solutions of polymer in a monomolecular solvent, 2) Guggenheim-DiMarzio approximation [59,60], which is based on calculating the number of possible ways of packaging rigid k-mers on lattices with different coordination numbers 3) the approximation based on the extension of the exact solution for a one-dimensional case [52,53] to higher dimensions [49,61], 4) well known quasichemical approximation [62] and mean-field approximation [63], 5) fractional statistical theory (FSTA) for the adsorption of polyatomic molecules, based on Holdan statistics [64], 6) semi-empirical model [61,65], etc. Unfortunately, none of these approximations is universal, and each shows quite good results, depending on the parameters of the model -a flexible or rigid k-mer, the length of k-mer, the presence or absence of lateral interactions between adsorbed molecules, etc.…”
Section: The Models Of Dimer and K-mer Adsorptionmentioning
confidence: 99%
“…Unfortunately, none of these approximations is universal, and each shows quite good results, depending on the parameters of the model -a flexible or rigid k-mer, the length of k-mer, the presence or absence of lateral interactions between adsorbed molecules, etc. A brief description of the approximations and compare them with each other can be found in [49,65]. Generally, more recent analytical approximations for the k-mers adsorption include earlier ones as special cases.…”
Section: The Models Of Dimer and K-mer Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation